2004
DOI: 10.1051/gse:2003055
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the proportion of genetically unbalanced spermatozoa in the semen of boars carrying chromosomal rearrangements using FISH on sperm nuclei

Abstract: -Many chromosomal rearrangements are detected each year in France on young boars candidates for reproduction. The possible use of these animals requires a good knowledge of the potential effect of the rearrangements on the prolificacy of their mates. This effect can be estimated by an accurate determination of the rate of unbalanced spermatozoa in the semen of boars which carry the rearrangements. Indeed, these spermatozoa exhibiting normal fertilizing ability are responsible for an early embryonic mortality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…The percentage of disomic/diploid spermatozoa, albeit very low (0.2%), was significantly higher in semen from inversion carriers than from the control (0.05%). This result is in accordance with disomy/ diploidy rates found for other inversions (Massip et al 2009) and reciprocal translocations (Pinton et al 2004;Massip et al 2008).…”
Section: Male Meiotic Segregation Patternssupporting
confidence: 93%
See 1 more Smart Citation
“…The percentage of disomic/diploid spermatozoa, albeit very low (0.2%), was significantly higher in semen from inversion carriers than from the control (0.05%). This result is in accordance with disomy/ diploidy rates found for other inversions (Massip et al 2009) and reciprocal translocations (Pinton et al 2004;Massip et al 2008).…”
Section: Male Meiotic Segregation Patternssupporting
confidence: 93%
“…Sperm preparation and hybridization were carried out according to the protocol described by Pinton et al (2004). Oocyte culture, maturation, and hybridization were carried out according to Pinton et al (2009).…”
Section: Spermfish and Fish On Metaphase II Of Matured In Vitro Oocytesmentioning
confidence: 99%
“…Two sperm-FISH experiments were carried out according to Pinton et al [56], one with BAC clones 227E10 and 421B09 revealed respectively with Alexa 594 and Alexa 488 and one with BAC clones 981H08 (for chromosome Y) and 227E10 revealed respectively by Alexa 488 and Alexa 594. The slides were observed under a Zeiss Axioskop microscope fitted with a triple bandpass filter and only sperm heads exhibiting high intensity signals were scored.…”
Section: Methodsmentioning
confidence: 99%
“…Economic analyses carried out for several translocations, including t(7;13)(q13;q46) found in Polish pigs, showed significant financial losses related to the use of a carrier boar both in AI and commercial herds (Danielak-Czech et al 1996;Pinton et al 2004). For that reason, several European countries have initiated karyotype control programmes of hypoprolific boars, which allowed identification of numerous chromosomal rearrangements (mainly reciprocal translocations) and elimination of their carriers from breeding.…”
mentioning
confidence: 99%
“…For that reason, several European countries have initiated karyotype control programmes of hypoprolific boars, which allowed identification of numerous chromosomal rearrangements (mainly reciprocal translocations) and elimination of their carriers from breeding. Moreover, the development of AI during the last decade has resulted in modification and intensification of cytogenetic evaluation systems, which concentrated especially on young purebred AI boars analysed before reproduction (Ducos et al 2002;Pinton et al 2004). …”
mentioning
confidence: 99%